Impact of communication barriers on urban development of Nowogród Bobrzański = Wpływ układu komunikacyjnego na prawidłowy rozwój urbanistyczny na przykładzie Nowogrodu Bobrzańskiego - Laskowski, Janusz; Juszczyk, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Network communication links is an indispensable element of development shaping. Any change in the way of using area should be preceded by an analysis of future impact taking into account the transport capacity. The development of buildings without adequate communication links leads to restrictions on object access, consequently it may lead to dangerous mishaps. Avoiding this type of situation is possible by carrying out sustainable development. The paper describes the relationship between the road system and urban layout on the example of Nowogród Bobrzański part of the city. One presented existing changes in the transportation system and its impact on local residents.
Keywords: komunikacja; układ urbanistyczny; droga; Nowogród Bobrzański; communication; urban layout; road